Clinical Significance and Expression of PAF and TNF-alpha in Seminal Plasma of Leukocytospermic Patients - Chaodong Liu; Hongjian Liu; Xianzhong Wang; Sun Xinbo (Hindawi Limited, 2012)
Objective. Discuss the changes and roles of PAF in the reproductive tract infection by observing the expression of platelet activating factor (PAF) and tumor necrosis factor α (TNF-α) in seminal plasma of patients with leukocytospermia. Methods. The seminal plasma was obtained from 22 cases of leukocytospermia and 15 cases of normal males; the peroxidase dyeing method was adopted for seminal plasma white blood count; the ELISA was adopted to test PAF and TNF-α concentration in seminal plasma. Result. PAF concentration ( ng/mL) of leukocytospermia group was significantly lower than the normal group ( ng/mL, ) while TNF-α ( ng/mL) was significantly higher than that of normal group ( ng/mL). There was negative correlation between PAF and TNF-α , (, ); the same situation existed in PAF and WBC (, ); but TNF-α was positively correlated to WBC (, ). Conclusion. (1) Low expression of PAF and high expression of TNF-α in leukocytospermia affect the sperm motility, which is one of the reasons that leads to infertility. (2) Lower expression of PAF has its particularity during the reproductive tract infection.